Cauchy wavelet transform of ultra-distributions in tube domains - Pathak R.S.; Upadhyay S.K. (My University, 2025)
In this paper, Cauchy wavelet transform of ultra-distributions in tube domains is defined and its various properties are studied using the theory of Cauchy integrals and Poisson integrals of ultra-distributions. © 2015 Taylor & Francis.